A study of double jeopardy: a comparison between article 7(2) of federal constitution and the position in England / Aimi Nadiah Abd Rahman, Saira Nur Farrin Baharin, Nur Farzana Mohd Puat - Abd Rahman, Aimi Nadiah; Baharin, Saira Nur Farrin; Mohd Puat, Nur Farzana (2008)
This research was conducted to critically analyse the comparison between Article 7(2) of Federal Constitution of Malaysia and the position in England on double jeopardy. We chose this topic because we want to know the ways in which the courts in Malaysia or England interpret double jeopardy whether it is wider or narrower. Moreover, recently there have been so many cases were the accused had been acquitted because of the lack of evidence to convict them. This is because there is lacuna in our law to recharge them if there is new evidence found. This led to the feeling of dissatisfaction on the part of the victim because they cannot get justice on their part. This research can open up our minds to the subject and also we can draw our own conclusion and recommendations for this research. Therefore, this issue needs more discussion and explanation for future benefits.